Adding Soy Protein to Milk Enhances the Effect of Resistance Training on Muscle Strength in Postmenopausal Women - Orsatti, Fábio L.; Maestá, Nailza [UNESP]; de Oliveira, Erick P.; Nahas Neto, Jorge [UNESP]; Burini, Roberto C. [UNESP]; Nunes, Paulo R. P.; Souza, Aletéia P.; Martins, Fernanda M.; Nahas, Eliana P. [UNESP] (Taylor & Francis, 2018)
Resistance training (RT) and high-quality protein ingestion improves muscle mass (MM) and strength (MS). However, no study has evaluated the effect of ingesting milk plus soy protein (SOY) on MM and MS in postmenopausal women (PW). Thus, the aim of this study was to evaluate the effects of adding SOY to milk on MM and MS after 16 weeks of RT. Thirty-two PW were randomized and allocated into two groups: placebo and RT (PL+RT, n = 16) and SOY and RT (SOY+RT, n = 16). The SOY+RT received 25 g of SOY while the PL+RT received 25 g of maltodextrin (placebo). All supplements were given in the form of a chocolate-flavored powder added to 200 mL of milk. The RT protocol consisted of eight total body exercises at 70% of one repetition maximum (1RM), three sets of 8–12 repetitions, 2–3 times/week. No differences were found in the baseline measures between groups (age, menopause status, anthropometric and nutrition patterns), except for protein intake, which was higher in the SOY+RT. Both groups increased the MM (bioimpedance) showing no difference between groups (PL+RT = 1.5 kg; SOY+RT = 1.1 kg). For MS, the SOY+RT showed a larger (p <.05) increase in 1RM of bench press (PL+RT = 6.7 kg; SOY+RT = 12.5 kg), knee extension (PL+RT = 3.7 kg; SOY+RT = 6.7 kg), total load (PL+RT = 15.1 kg; SOY+RT = 24.2 kg), and the total load exercises/MM (PL+RT = 0.3 kg; SOY+RT = 0.9 kg). These results suggest that adding SOY to milk combined with 16 weeks of RT resulted in more significant increases in MS in PW.
Keywords: menopause; sarcopenia; supplementation; weight-lifting exercise program